Twitter and reflection: tweeting towards deeper learning. Issue 4 (3rd July 2020) - Corrales, Kathleen A.; Erwin, Trey Collier
ABSTRACT: Student reflection is commonly thought to be associated with enhanced learning, especially when it involves connecting course learning to personal experience. In this mixed-methods study, we viewed 670 reflective tweets from 105 students in advanced English language courses at a private university in Latin America to measure the relationship between the depth of reflection of student tweets and their learning as demonstrated through their exam scores. We also applied a survey to capture students' self-perceived ability to write deep reflections and the extent to which they believe this helped them succeed in the course. The result of regression analysis revealed a correlation between deeper reflections and better performance on student exams. We also found that students tended to overestimate their abilities to write deep reflections as the majority of tweets were more superficial. Furthermore, many students did not see a direct connection between their reflective practice and their final grade in the course but viewed reflection positively in terms of contributing to their learning.